Symptoms of Common Mental Disorders and Adverse Health Behaviours in Male Professional Soccer Players - Gouttebarge, Vincent (J Hum Kinet, 2015)
To present time, scientific knowledge about symptoms of common mental disorders and adverse health behaviours among professional soccer players is lacking. Consequently, the aim of the study was to determine the prevalence of symptoms of common mental disorders (distress, anxiety/depression, sleep disturbance) and adverse health behaviours (adverse alcohol behaviour, smoking, adverse nutrition behaviour) among professional soccer players, and to explore their associations with potential stressors (severe injury, surgery, life events and career dissatisfaction). Cross-sectional analyses were conducted on baseline questionnaires from an ongoing prospective cohort study among male professional players. Using validated questionnaires to assess symptoms of common mental disorders and adverse health behaviours as well as stressors, an electronic questionnaire was set up and distributed by players’ unions in 11 countries from three continents. Prevalence of symptoms of common mental disorders and adverse health behaviours among professional soccer players ranged from 4% for smoking and 9% for adverse alcohol behaviour to 38% for anxiety/depression and 58% for adverse nutrition behaviour. Significant associations were found for a higher number of severe injuries with distress, anxiety/depression, sleeping disturbance and adverse alcohol behaviour, an increased number of life events with distress, sleeping disturbance, adverse alcohol behaviour and smoking, as well as an elevated level of career dissatisfaction with distress, anxiety/depression and adverse nutrition behaviour. Statistically significant correlations (p<0.01) were found for severe injuries and career dissatisfaction with most symptoms of common mental disorders. High prevalence of symptoms of common mental disorders and adverse health behaviours was found among professional players, confirming a previous pilot-study in a similar study population.